THROMBOTIC MICROANGIOPATHY AS THE FIRST MANIFESTATION OF DISSEMINATED MALIGNANT DISEASE - Todorovic, Zeljko; Andjelic, Marko (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Thrombotic microangiopathies are a group of diseases characterized by disseminated intravascular thrombosis, thrombocytopenia and ischemic organ damage. This group includes thrombotic thrombocytopenic purpura and hemolytic-uremic syndrome. One of the causes of thrombotic microangiopathy, although rare, can also be malignant diseases, primarily cancers of the stomach, prostate, breast and lungs.Case report: We present a patient with thrombotic microangiopathy and disseminated malignant disease of unclear etiology. Conclusion: This clinical entity is called carcinoma-associated thrombotic microangiopathy and was first described in 1970. However, only a few dozen cases have been described to date. Considering the high mortality, it should be considered in patients with malignant disease, microangiopathic hemolytic anemia, and thrombocytopenia.
Keywords: thrombotic microangiopathy; thrombotic thrombocytopenic purpura; hemolytic-uremic syndrome